The Key Success Factors of Fraser & Neave (F&N) - Chiew Shi Yee; Daisy Mui Hung Kee; Chin Joo Yi; Nur Fatin Najihah; Muhammad Khairul Wafiq; Lavi Sharma; Rudresh Pandey (International Journal of Applied Business and International Management, 2020)
This study aims to examine the key factors that drive the success of Fraser & Neave (F&N). The data collection was by referring to the company’s official website and other related websites. Identified key success factors are innovation, consumer’s health and safety, creating value for society, talent management, and sustainable sourcing. These empirical findings provide new insights for the management of F&N about the antecedents of governing talent development. This study also provides a breakdown of F&N's strategic pillars and factors affecting those strategies, which can be utilized by management for future decision making to achieve their goals.